COGNITIVE DEVELOPMENT IN PRESCHOOL CHILDREN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this article, the importance of cognition, memory, thinking, attention in the mental development of preschool children, the processes of emotional cognition in the study of things and events, that is, children's perception of the environment through sight, hearing, smell, full perception During this period, the formation of the child as a person, the first perception of the world through the objects and things around him, the desire to find meaning in it, the development of interests and feelings are highlighted.